WOLNOŚĆ KOALICJI ZWIĄZKOWEJ PRACOWNIKÓW NIETYPOWYCH, OSóB ZATRUDNIONYCH NA PODSTAWIE UMÓW CYWILNOPRAWNYCH I SAMOZATRUDNIONYCH - Reda-Ciszewska, Anna (Zeszyty Prawnicze, 2016)
FREEDOM OF ASSOCIATION OF ATYPICAL EMPLOYEES, PERSONS EMPLOYED ON THE GROUNDS OF CIVIL CONTRACTS, AND THE SELF-EMPLOYED Summary This article discusses the freedom of association of atypical employees, persons employed on the grounds of civil law contracts, and the selfemployed. Polish law guarantees the right of association to employees on the grounds of its labour law (kodeks pracy). However, the International Labour Organisation Convention denies the right of association to members of the armed forces, police, and public administration. In 2011 a complaint was submitted to the Committee on Freedom of Association, which has drawn up recommendations for Polish law. The author analyses the solutions of Polish law in the context of the Committee’s recommendations on freedom of association for atypical employees, persons employed on a civil law contract, and the self-employed.